2001
DOI: 10.1126/science.1055465
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Oscillatory Neuronal Synchronization by Selective Visual Attention

Abstract: In crowded visual scenes, attention is needed to select relevant stimuli. To study the underlying mechanisms, we recorded neurons in cortical area V4 while macaque monkeys attended to behaviorally relevant stimuli and ignored distracters. Neurons activated by the attended stimulus showed increased gamma-frequency (35 to 90 hertz) synchronization but reduced low-frequency (<17 hertz) synchronization compared with neurons at nearby V4 sites activated by distracters. Because postsynaptic integration times are sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

166
1,979
11
20

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 2,542 publications
(2,211 citation statements)
references
References 32 publications
166
1,979
11
20
Order By: Relevance
“…ART also predicted that matching synchronizes the firing patterns of cells coding matched stimuli and thereby facilitates fast stable learning (cf., Engel et al, 2001;Fries et al, 2001;Grossberg, 1976Grossberg, , 1980Grossberg, , 1999Pollen, 1999;Usrey, 2002). SMART further develops that proposal to include spiking neurons and the role of the higher-order specific and nonspecific thalamic nuclei.…”
Section: 21mentioning
confidence: 99%
“…ART also predicted that matching synchronizes the firing patterns of cells coding matched stimuli and thereby facilitates fast stable learning (cf., Engel et al, 2001;Fries et al, 2001;Grossberg, 1976Grossberg, , 1980Grossberg, , 1999Pollen, 1999;Usrey, 2002). SMART further develops that proposal to include spiking neurons and the role of the higher-order specific and nonspecific thalamic nuclei.…”
Section: 21mentioning
confidence: 99%
“…In vivo studies have also revealed evidence for phase locking in the neocortex 57 . In cortical area V4, the correlation in the gamma frequency range between spike trains and the LFP near the recorded neuron increased during attention 56,57 . Similarly, in a behavioural task in which a monkey had to hold a stimulus in working memory 68 , locking of spikes to the theta oscillation was increased in response to a neuron's preferred stimulus compared with a non-preferred stimulus, independent of changes in the neuron's firing rate.…”
Section: Evidence For Phase Locking In Vivomentioning
confidence: 99%
“…Electroencephalograms (EEGs) recorded from the human scalp exhibit superposed rhythms in various frequency ranges, including the delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (12-30 Hz) and gamma (30-80 Hz) ranges 54 . The strength of these rhythms changes over time and depends on behavioural states and cognitive processes [55][56][57] . The rhythms arise from large-scale, coherent firing of neurons.…”
Section: The Contribution Of Cortical Oscillations To Precisionmentioning
confidence: 99%
“…Cortical gamma-band activity in general has been found to be involved in many cortical processes (Tallon-Baudry, 2009;Fries, 2009), and might serve as a mechanism for efficient neuronal communication and processing (Fries, 2005). Gamma activity has been related to important brain functions such as visual (Hoogenboom et al, 2006) and tactile processing (Bauer et al, 2006), memory (Jensen et al, 2007;van der Werf et al, 2008), attention (Fries et al, 2001), and motor control (Schoffelen et al, 2005). Behaviorally, the strength of gamma correlates with reaction times (Womelsdorf et al, 2006;Hoogenboom et al, 2010).…”
Section: Eccentricity Effectmentioning
confidence: 99%
“…Gamma-band synchronization is observed during visual (Hoogenboom et al, 2006;Muthukumaraswamy et al, 2009), somatosensory (Bauer et al, 2006), and auditory (Brosch et al, 2002) stimulation; it is involved in memory processes (Fell et al, 2001;Howard et al, 2003) and motor control (Brown et al, 1998;Schoffelen et al, 2005). It is enhanced during attention (Fries et al, 2001;Bosman et al, 2012), and its moment-by-moment fluctuations predict the behavioral benefits of attention (Womelsdorf et al, 2006;Hoogenboom et al, 2010). Gamma synchronization is also affected in cognitive disorders, notably schizophrenia, with patients showing lower gamma power than healthy controls (see Uhlhaas and Singer (2010), for a review).…”
Section: Introductionmentioning
confidence: 99%